Tourism branding Komunikasi Pemasaran Ekonomi Kreatif sebagai Upaya Peningkatan Kesejahteraan Masyarakat Desa Wisata Budaya Plunturan, Kecamatan Pulung, Ponorogo - Ekoputro, Widiyatmo; Nugroho, Mulyanto Nugroho (Universitas 17 Agustus 1945 Surabaya, 2021)
Plunturan Village, Pulung Subdistrict, Ponorogo Regency as a research location wants joint efforts in all matters, especially efforts to mobilize all potential optimally so that the village economy can increase, hoping that the results will be directly proportional to the welfare of the community. The purpose of this research is to find out the communication built internally in the Plunturan village community through groups of small and medium enterprises and groups of actors and cultural observers has been running well, so that in the future there is a need for a breakthrough in the media to further empower the community's abilities, one of which is using the media. social society which so far is still loved by the general public, especially millennials. The method used in this study to achieve the target to be achieved using qualitative methods, with observation techniques and in-depth interviews with informants. The results of this research can then be developed and used by the community. The use of social media technology is an effort to build an image so that the wider community knows more about the potential that exists in Plunturan village as a tourist destination that has characteristics with local wisdom that must be visited by domestic and foreign tourists.Keywords: Tourism Brading, Marketing Communication, Creative Economy